Effect of COVID-19 vaccination on the incidence, lethality and mortality of pregnant and postpartum women - Marcela de Andrade Pereira Silva; Fernando Castilho Pelloso; Maria Dalva de Barros Carvalho; Rosana Rosseto de Oliveira; Constanza Pujals; Stéfane Lele Rossoni; Natan Nascimento de Oliveira; Mirella Machado Ortiz Modesto; Deise Helena Pelloso Borghesan; Ana Carolina Jacinto Alarcão; Vlaudimir Dias Marques; Marcia Edilaine Lopes Consolaro; et al. (PLoS ONE, 2025)
Objectives To analyze the incidence of Severe Acute Respiratory Syndrome (SARS), lethality and mortality of Brazilian pregnant and postpartum women infected with SARS-CoV-2, before and after vaccination against Covid-19. Methods This is an ecological study of time series, carried out with secondary data from the Brazilian Ministry of Health, from March 2020 to April 2024. Slopes and trend changes in the time series were identified by Mann-Kendall and generalized fluctuation tests, respectively. The series was modeled using Generalized Additive Models with interaction between time and start of vaccination. A Pearson correlation was used between the number of accumulated doses and the incidence, lethality and mortality rates, in addition to comparing the average rates before and after the vaccination peak of the first dose using ANOVA. Results Significant temporal variations were observed in the incidence rates of SARS, lethality and mortality in pregnant and postpartum women with SARS-CoV-2, before and after vaccination against Covid-19 in Brazil, with a significant decreasing trend after the start of vaccination. It was observed that time alone did not show a significant effect on the reduction of lethality and mortality rates, which occurred only when there was an interaction effect between time and the start of vaccination. The accumulated doses of the vaccine correlated with the decrease in the analyzed rates, which explained 39.18% of variation in the incidence rate, 43.34% in the lethality rate, and 34.81% in the mortality rate. The monthly averages of the incidence, lethality, and mortality rates before and after vaccination reduced significantly. Conclusions The findings of this study indicate that vaccination against Covid-19 in Brazilian pregnant and postpartum women had a positive effect on reducing the incidence of SARS by SARS-CoV-2, lethality and mortality rates in the obstetric population.